PENGGUNAAN OBAT ANTIDIABETES PADA PASIEN RAWAT INAP DI RUMAH SAKIT HARAPAN PEMATANGSIANTAR: PENGGUNAAN OBAT ANTIDIABETES PADA PASIEN RAWAT INAP DI RUMAH SAKIT HARAPAN PEMATANGSIANTAR - Ricard Fredrik Marpaung; Pinondang Hotria; Shofian Syarifuddin (LPPM Universitas Abdurrab, 2021)
ABSTRACT Diabetes mellitus (DM) is a global health problem whose incidence is increasing. As many as 346 million people in the world suffer from diabetes, and it is estimated that it will reach 380 million in 2025. According to WHO in 2000, Indonesia is in the fourth of the country with the highest prevalence of diabetes in the world with a number of sufferers of 8.4 million people. The purpose of this study was to determine the pattern of diabetes mellitus drug use at the Harapan Hospital in Pematangsiantar for the period January-March 2020 and to evaluate the antidiabetic drugs which included the righ indication, right dose, right patient, right drug, and the right way of administration. The research was a survey with a retrospective method, the design used was cross sectional, namely the collection of variable data to get an overview of the use of antidiabetic drugs in inpatients at Harapan Hospital in Pematangsiantar for the period January-March 2020. The results showed that patients suffering from diabetes mellitus in The Harapan Hospital period January-March 2020 were more female than male, with 25 female patients (55.6%) and 20 male patients (44.4%). The highest distribution of antidiabetic single-administered was Glimepiride, namely 11 prescriptions (24.4%) and the highest combination was Glimepiride with Metformin 5 prescription (11.1%). The results of the rationality evaluation showed that the use of antidiabetic drugs has the right indication, the right dose, the right patient, the right drug and the right way of administration